2013
DOI: 10.1371/journal.pone.0076612
|View full text |Cite
|
Sign up to set email alerts
|

An MRI-Visible Non-Viral Vector Bearing GD2 Single Chain Antibody for Targeted Gene Delivery to Human Bone Marrow Mesenchymal Stem Cells

Abstract: The neural ganglioside GD2 has recently been reported to be a novel surface marker that is only expressed on human bone marrow mesenchymal stem cells within normal marrow. In this study, an MRI-visible, targeted, non-viral vector for effective gene delivery to human bone marrow mesenchymal stem cells was first synthesized by attaching a targeting ligand, the GD2 single chain antibody (scAbGD2), to the distal ends of PEG-g-PEI-SPION. The targeted vector was then used to condense plasmid DNA to form nanoparticle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Since particles can be readily functionalised [28,29], the exploitation of their magnetic properties has been envisaged for magnet-driven drug delivery approaches, whereby particles might act as vector for a therapeutic drug or cargo which could be localised through magnet exposure, for applications in joint, spinal cord, ear and eye treatments for instance [30,31,32]. Building on this concept of magnetic targeting, the use of iron oxide particles to label cells intracellularly has also been proposed as a way to confer them magneto-responsiveness [2,3,33].…”
Section: Discussionmentioning
confidence: 99%
“…Since particles can be readily functionalised [28,29], the exploitation of their magnetic properties has been envisaged for magnet-driven drug delivery approaches, whereby particles might act as vector for a therapeutic drug or cargo which could be localised through magnet exposure, for applications in joint, spinal cord, ear and eye treatments for instance [30,31,32]. Building on this concept of magnetic targeting, the use of iron oxide particles to label cells intracellularly has also been proposed as a way to confer them magneto-responsiveness [2,3,33].…”
Section: Discussionmentioning
confidence: 99%
“…61,62 Studies have also suggested nanoparticle-based transfection of MSCs to be comparable or more efficient than lipofectamine. 63-65 Through the proton-sponge effect, positively charged nanoparticles can facilitate DNA uptake through endocytosis and evade the lysosome for delivery to the nucleus. 8 Furthermore, enhanced transfection can be accomplished through introduction of magnetic fields to target SPION–DNA complexes to desired sites throughout the body, and once there, reduce free diffusion of these particles.…”
Section: Nanoparticle-based Deliverymentioning
confidence: 99%
“…As this marker has been found to be expressed on the surface of MSCs, GD2 antibodies conjugated to the distal ends of PEG-g-PEI SPIONs increased labeling of human MSCs and delivery of plasmid DNA. 65 Importantly, while nanoparticles have been shown to be suitable for efficient in vivo tacking of cells through MRI, ongoing investigations continue to evaluate whether these tags may interfere with cellular function and osteogenic differentiation capacity. In vitro studies have shown relative innocuousness of SPION and gold nanoparticles, however other reports suggest certain nanoparticles to interfere with bone forming capacity of MSCs in vivo .…”
Section: Nanoparticle-mediated Stem Cell Labeling/targetingmentioning
confidence: 99%
“…This facilitates the efficiency of the subsequent gene loading process, as well as the binding of UCNPs to the anionic plasma membrane. The cellular attachment and tissue specificity of the nanoparticles can be enhanced by conjugating ligands (such as folic acid, 66 , 67 galactose, 68 transferrin, 66 , 69 RGD peptide, 70 , 71 and antibodies 72 , 73 ) to the nanoparticle surface for receptor-mediated endocytosis. The feasibility of this has been evidenced by an earlier study, in which folic acid and anti-Her2 antibody have been conjugated to silica-coated NaYF 4 :Yb,Er UCNPs.…”
Section: Molecular Design Of Ucnps As Gene Carriersmentioning
confidence: 99%